GFRα1 released by nerves enhances cancer cell perineural invasion through GDNF-RET signaling - He, Shuangba (National Academy of Sciences, 2014)
The ability of cancer cells to invade along nerves is associated with aggressive disease and diminished patient survival rates. Perineural invasion (PNI) may be mediated by nerve secretion of glial cell line-derived neurotrophic factor (GDNF) attracting cancer cell migration through activation of cell surface Ret proto-oncogene (RET) receptors. GDNF family receptor (GFR)α1 acts as coreceptor with RET, with both required for response to GDNF. We demonstrate that GFRα1 released by nerves enhances PNI, even in the absence of cancer cell GFRα1 expression. Cancer cell migration toward GDNF, RET phosphorylation, and MAPK pathway activity are increased with exposure to soluble GFRα1 in a dose-dependent fashion. Dorsal root ganglia (DRG) release soluble GFRα1, which potentiates RET activation and cancer cell migration. In vitro DRG coculture assays of PNI show diminished PNI with DRG from GFRα1(+/−) mice compared with GFRα1(+/+) mice. An in vivo murine model of PNI demonstrates that cancer cells lacking GFRα1 maintain an ability to invade nerves and impair nerve function, whereas those lacking RET lose this ability. A tissue microarray of human pancreatic ductal adenocarcinomas demonstrates wide variance of cancer cell GFRα1 expression, suggesting an alternate source of GFRα1 in PNI. These findings collectively demonstrate that GFRα1 released by nerves enhances PNI through GDNF-RET signaling and that GFRα1 expression by cancer cells enhances but is not required for PNI. These results advance a mechanistic understanding of PNI and implicate the nerve itself as a key facilitator of this adverse cancer cell behavior.